Pengaruh Pengalaman Auditor, Tekanan Batas Waktu Audit dan Locus Of Control Internal Pada Skeptisisme Profesional Auditor - Oktaviani, Nyoman Ayu; Latrini, Made Yenni (E-Jurnal Akuntansi; Vol 24 No 3 (2018)DO - 10.24843/EJA.2018.v24.i03.p11, 2018)
This study aims to examine the effect of auditor experience, audit time deadline pressure, and internal locus of control on professional skepticism of auditors. This research was conducted at Public Accounting Firm in Bali. The samples used were 44 auditors using nonprobability sampling method and purposive sampling technique. Data were collected by using questionnaire method. Data analysis technique used is Multiple Linear Regression Analysis. The results of hypothesis testing show that the higher the auditor's experience in carrying out its audit duties, the auditor's professional skepticism is increasing. The more optimal the audit time deadline pressure is received by the auditor, it will support the auditor to improve his professional skepticism. The better the locus of control of the internal auditor, the higher the professional skepticism the auditor has. Keywords : Auditor experience, audit time deadline pressure, locus of control internal auditor, professional skepticism auditor